1998
DOI: 10.1111/j.1365-2621.1998.tb15747.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Method for Quantification of Cholesterol in Turkey Meat and Products

Abstract: A direct saponification method was developed to determine cholesterol quantitatively in turkey meat and its processed products at a detection limit of 10 ppm. Five solvents and two derivatizing agents were evaluated. The method involved direct saponification with ethanolic KOH, homogeneous-phase toluene extraction of unsaponifiables, derivatization of cholesterol to a trimethylsilyl ether and quantitation by gas chromatography with flame ionization detection using 5␣-cholestane as internal standard. Compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…Similar phenomena were discussed by Fenton (1992) and Lesellier (2001). For the purpose of cholesterol determination, (5%‐phenyl)‐methylpolysiloxane (HP‐5, HP‐5 ms, ZB‐5, SPB‐5, DB‐5, RTX‐5, HP‐Ultra2) with very low polarity has probably been the most commonly used stationary phase regardless of whether cholesterol was derivatized (Ulberth and Reich 1992; Rodriguez‐Palmero and others 1994; King and others 1998; Toivo and others 2001; Baggio and others 2002; Bowden and others 2009; Isidorov and Szczepaniak 2009; Schummer and others 2009). The film thickness of choice was 0.25 μm except when there was no derivatization (1.05 μm, King and others 1998).…”
Section: Cholesterol Analytical Methods In Meat and Poultry Productsmentioning
confidence: 56%
See 3 more Smart Citations
“…Similar phenomena were discussed by Fenton (1992) and Lesellier (2001). For the purpose of cholesterol determination, (5%‐phenyl)‐methylpolysiloxane (HP‐5, HP‐5 ms, ZB‐5, SPB‐5, DB‐5, RTX‐5, HP‐Ultra2) with very low polarity has probably been the most commonly used stationary phase regardless of whether cholesterol was derivatized (Ulberth and Reich 1992; Rodriguez‐Palmero and others 1994; King and others 1998; Toivo and others 2001; Baggio and others 2002; Bowden and others 2009; Isidorov and Szczepaniak 2009; Schummer and others 2009). The film thickness of choice was 0.25 μm except when there was no derivatization (1.05 μm, King and others 1998).…”
Section: Cholesterol Analytical Methods In Meat and Poultry Productsmentioning
confidence: 56%
“…Cholesterol can be derivatized to the TMS ether by many different reagents (see summaries by Fenton 1992 and Abidi 2001). King and others (1998) compared the TMS derivatization process by hexamethyldisilane (HMDS)/trimethylchlorosilane (TMCS) (Sigma, St. Louis, Mo., U.S.A.) and Sylon BTZ (N‐trimethylsilylimidazole [TSIM]/N,O‐bis(trimethylsilyl)acetamide [BSA]/TMCS 3:3:2) (Supelco, Bellefonte, Pa., U.S.A.) and reported that the results were comparable (not statistically tested); however, Sylon BTZ reagent was faster and consumed less solvent. In contrast, Nawar and others (1991), when optimizing the silylating conditions for cholesterol and its oxides with N,O‐bis(trimethylsilyl)trifluoroacetamide (BSTFA), BSTFA/1% TMCS, and Sylon BTZ, found that BSTFA/1% TMCS gave the maximum conversion of cholesterol within 1 h at 80 °C and provided superior silylation for 7α‐ and 7β‐diols compared with BSTFA only.…”
Section: Cholesterol Analytical Methods In Meat and Poultry Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…The moisture, crude protein, crude fat and crude ash contents were then determined using the AOAC methods (AOAC, 2000). Additionally, the cholesterol concentration of the meat was determined according to the method described by King et al (1998) using a gas chromatograph (DS 6200, Donam Co., Seongnam, Gyeonggido, South Korea).…”
Section: Measurements and Analysismentioning
confidence: 99%